2018
DOI: 10.12659/msmbr.910307
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parkinson Disease Induction with Cardiac Upregulation of Apoptotic Mediators P53 and Active Caspase-3: An Immunohistochemistry Study

Abstract: BackgroundApoptosis plays a key role in the pathogenesis of Parkinson disease (PD). Active caspase-3, which is a proapoptotic factor, has been shown to reduce cardiac contractility, causing cardiac dysfunction in many pathological diseases. Reduced cardiac contractility and cardiac autonomic dysfunction have been reported in PD patients and PD mice treated with MPTP. The aim of this study was to show the impact of PD induction on the expression of the apoptotic mediators p53 and active caspase-3 in the heart.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Recent findings correlate PD and several apoptotic markers (the overexpression of p53 and active caspase-3 in the cardiac muscle) and the underexpression of the β-adrenergic receptor, which can potentially promote the cardiac dysfunction observed in PD patients. 20 Clinical and pathological studies have provided strong evidence of the involvement of cardiac sympathetic nerves in PD patients. [21][22][23][24] Our results demonstrate noradrenergic sympathetic loss (significant decrease in NA turnover in RV) in MPTP-treated monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings correlate PD and several apoptotic markers (the overexpression of p53 and active caspase-3 in the cardiac muscle) and the underexpression of the β-adrenergic receptor, which can potentially promote the cardiac dysfunction observed in PD patients. 20 Clinical and pathological studies have provided strong evidence of the involvement of cardiac sympathetic nerves in PD patients. [21][22][23][24] Our results demonstrate noradrenergic sympathetic loss (significant decrease in NA turnover in RV) in MPTP-treated monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several pieces of evidence suggest that dopamine-containing neurons' death may result from elevated reactive oxygen species levels, 1,[23][24][25] mitochondrial respiratory failure, 1,[26][27][28] and activation of the NF-κB and caspase pathways. 1,27,29,30 The development of inflammation and oxidative stress is often accompanied by dysbiosis or dysfunction of the gut microbiome. 31,32 The gut microbiome plays a vital role in human health and disease and is, therefore, a popular area of research.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α initiates and promotes the cell surface death receptor-mediated apoptosis. [31][32][33] Previous studies have demonstrated TNF-α overexpression in many neurodegenerative diseases, such as PD, Alzheimer disease (AD), and amyotrophic lateral sclerosis (ALS). [34][35][36][37] In addition, elevated levels of TNF-α have been shown in the cerebellar PCs in many pathological conditions.…”
Section: Discussionmentioning
confidence: 99%